Influence of 1‐methylcyclopropene (1‐MCP) on ripening and ethylene biosynthesis‐related enzyme gene expression in harvested blueberries. Issue 10 (2nd August 2021) - Zhang, Lei; Wu, Chunling
Abstract: The aim of the study was to discuss the effect of 1‐methylcyclopropene (1‐MCP) with and without ethylene on physiological indexes and ethylene biosynthesis genes expression in blueberries. Results showed that treatment of 1‐MCP alone, or with ethylene, improved firmness, soluble solids content, total phenols content, enzyme activities in comparison with control. Treatment with ethylene promoted respiratory action, decay incidence, and browning index comparing with untreated group. In addition, expression levels of AcACS1 and AcACO1 in 1‐MCP‐treated samples, or associated with ethylene, decreased for different levels during storage that confirmed 1‐MCP contributed to the downregulation of ethylene biosynthesis genes expression. Subsequent use of ethylene did not neutralize the effectiveness of 1‐MCP on maintaining commercial quality of blueberries. Practical applications: The results of this study were helpful to further understand the regulation mechanism of 1‐methylcyclopropene (1‐MCP) on ethylene biosynthesis genes, which provided theoretical basis for perfecting the fruit ripening theory and reference for the breakthrough of fruit storage and preservation technology. Further studies were needed to explore the action mechanism of 1‐MCP treatment on suppressing ethylene biosynthesis genes expression of blueberry fruits by genomics or proteomics techniques.